Effect of Co-Sputtered Copper and Titanium Oxide Coatings on Bacterial Resistance and Cytocompatibility of Osteoblast Cells - Maria P. Nikolova; Iliyan Tzvetkov; Tanya V. Dimitrova; Veronika L. Ivanova; Yordan Handzhiyski; Andreana Andreeva; Stefan Valkov; Maria Ormanova; Margarita D. Apostolova (Nanomaterials, 2024)
One of the primary risk factors for implant failure is thought to be implant-related infections during the early healing phase. Developing coatings with cell stimulatory behaviour and bacterial adhesion control is still difficult for bone implants. This study proposes an approach for one-step deposition of biocompatible and antimicrobial Cu-doped TiO2 coatings via glow-discharge sputtering of a mosaic target. During the deposition, the bias of the Ti6Al4V substrates was changed. Structure examination, phase analysis, and surface morphology were carried out using X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS). The hardness values and hydrophilic and corrosion performance were also evaluated together with cytocompatible and antibacterial examinations against E. coli and S. aureus. The results show great chemical and phase control of the bias identifying rutile, anatase, CuO, or ternary oxide phases. It was found that by increasing the substrate bias from 0 to −50 V the Cu content increased from 15.3 up to 20.7 at% while at a high bias of −100 V, the copper content reduced to 3 at%. Simultaneously, apart from the Cu2+ state, Cu1+ is also found in the biased samples. Compared with the bare alloy, the hardness, the water contact angle and corrosion resistance of the biased coatings increased. According to an assessment of in vitro cytocompatibility, all coatings were found to be nontoxic to MG-63 osteoblast cells over the time studied. Copper release and cell-surface interactions generated an antibacterial effect against E. coli and S. aureus strains. The −50 V biased coating combined the most successful results in inhibiting bacterial growth and eliciting the proper responses from osteoblastic cells because of its phase composition, electrochemical stability, hydrophilicity, improved substrate adhesion, and surface roughness. Using this novel surface modification approach, we achieved multifunctionality through controlled copper content and oxide phase composition in the sputtered films.